Thematic Content Analysis of Blended Learning Studies in the Field of Mathematics Education - Aslan, Seda Aktı (My University, 2022)
The goal of this research is to examine the methodological trends and outputs of blended learning studies focusing on mathematics education. Accordingly, thematic content analysis was used in the current research. Studies were screened through electronic databases which include Web of Science, SCOPUS, ERIC (Education Resources Information Center), ULAKBIM (the Turkish Academic Network and Information Centre), DergiPark (JournalPark) and CoHE Thesis Center (the Council of Higher Education in Turkey). After the keywords and filters specified in the databases were searched, a total of 1299 research and 72 thesis studies were determined. Among these studies, the PRISMA method was used to select the studies to be included in the current research. At the end of all reviews, 11 articles and 4 theses were included in the current research. The results of studies emphasized that blended learning affected students' views, problem solving skills, self-regulation skills and more than half of the independent variables positively.
Keywords: Mathematics education; thematic content analysis; Blended learning